Der heliopolitanische Türpfosten mit der 2. Annaleninschrift Sesostris’ I - Hernández, Roberto Díaz (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
A Heliopolitan inscription in a temple door post from Sesostris I’s times was published by Daressy in 1903. It has since then been almost entirely disregarded by Egyptologists despite its relevance on Sesostris I’s policy regarding endowments to Egyptian temples. This paper is the first historical and philological study of such a document and it aims to shed some new light on Sesostris I’s reign. It comprises four parts —dating and purpose of the temple door post (I); general remarks on the text (II); transcription and transliteration (III); explanatory notes (IV).